The Effect of User Experience (UX) Design on Learning Management Systems on Student Motivation, Collaboration, and Learning Outcomes: A Quasi-Experimental - Saona, Saona; Alifah, Nur; Zuhriyah, Nabilaa Faizatuz (Jurnal Pendidikan Indonesia, 2026)
Online learning in higher education increasingly relies on Learning Management Systems (LMS), but the quality of the user experience (UX) often determines the level of student engagement and learning outcomes. This study aims to: (1) analyze the effect of improved LMS UX on student learning motivation, (2) evaluate the effect of improved LMS UX on the quality and intensity of student collaboration, and (3) examine the effect of improved LMS UX on learning outcomes by controlling for prior ability (pretest). The research method used a quasi-experimental design with a nonequivalent control group pretest–posttest. The sample consisted of two classes: the experimental group used an LMS with improved UX, while the control group used a standard LMS. Data were collected through motivation and collaboration questionnaires, learning outcome tests (pretest–posttest), and LMS activity logs, then analyzed using ANCOVA with the pretest as a covariate. The results showed that: (1) the learning motivation of the experimental group increased more than that of the control group, (2) student collaboration in the experimental group was more intense and of higher quality, and (3) the learning outcomes of the experimental group were higher after controlling for initial abilities. In conclusion, improving the UX of LMS contributes positively to student motivation, collaboration, and learning outcomes in online learning.